(untitled) (Research, Society and Development, 2022)
Sustainability has been increasingly discussed because it is a necessity. Adopting sustainable measures is one way we must protect the environment. There are many ways we can implement in our daily lives to mitigate the impacts generated, among them we can properly manage waste, reuse and recycle as much as possible, implement rainwater reuse systems and use solar energy. By adopting measures such as these in the economic, social and environmental spheres, we can say that we are exercising sustainability. In this context, the present work has as objective the elaboration of a roadmap for water management for popular houses, elaborating actions that lead to the reduction of water waste and better reuse of them. Therefore, a case study was carried out in a single-family residence of 216m², showing the results of each stage. From the result, it can be concluded that gray water reuse and rainwater reuse systems are clear and real, contribute to water conservation, as they reduce the consumption of drinking water for less noble purposes and contribute to sustainability. water in cities.